2010
DOI: 10.4317/medoral.15.e310
|View full text |Cite
|
Sign up to set email alerts
|

Oral status and Candida colonization in patients with Sjogren s Syndrome

Abstract: Objective: To determine the oral status, salivary flow rate,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
48
2
6

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(63 citation statements)
references
References 17 publications
7
48
2
6
Order By: Relevance
“…Ergun et al found out a significant difference between patients with SS and healthy controls in regard to API and BOP (78). This result is in agreement with the studies which have found that the API, PPD and BOP are significantly higher in SS patients than healthy subjects (75)(76)(77)79).…”
Section: Periodontal Statussupporting
confidence: 80%
See 1 more Smart Citation
“…Ergun et al found out a significant difference between patients with SS and healthy controls in regard to API and BOP (78). This result is in agreement with the studies which have found that the API, PPD and BOP are significantly higher in SS patients than healthy subjects (75)(76)(77)79).…”
Section: Periodontal Statussupporting
confidence: 80%
“…Studies which evaluated the periodontal status of the patients with Sjögren's syndrome (GCF: gingival creviculer fluid, DMF-T: decayed, missing, and filled permanent teeth, HS: healthy subjects, S: statistical significant; NS: not statistical significant) (78).…”
Section: Periodontal Statusmentioning
confidence: 99%
“…19,26 Studies in oral health show that pSS patients have a diminished salivary flow with consequent high incidence of dental caries, increased susceptibility to oral candidiasis, tooth loss, greater periodontal destruction, pain symptoms during chewing, speech difficulties, tongue palpitation and angular cheilitis. 5,6,27,28,29,30,31,32 The present study demonstrated that the decreased salivary flow in pSS patients was associated with higher PI, and a significant imbalance between the concentration of pro-and anti-inflammatory cytokines. Furthermore, it was observed that periodontal treatment of pSS patients can lead to increased salivary flow and improved ESSPRI.…”
Section: Discussionmentioning
confidence: 69%
“…3 Compromised salivary flow and consequent higher dental plaque index are associated with increased prevalence of chronic periodontitis in pSS patients. 4,5,6 In fact, Celenligil et al 7 observed a higher presence of serum antibodies against periodontal pathogens such as Aggregatibacter actinomycetemcomitans (Aa) and Porphyromonas gingivalis (Pg) in pSS patients, compared with healthy subjects with severe chronic periodontitis. Interestingly, Lugonja et al 8 also found raised serum antibody levels to Prevotella denticola in pSS patients, compared with a non-inflammatory group of patients with osteoarthritis.…”
Section: Introductionmentioning
confidence: 99%
“…(i) We assume that the combination of neutral pH, hemin, and no CO 2 , which gives the shortest branching time (Figures 2 and 4), is a suitable model of the oral cavity [20], where bleeding occurs frequently as a result of a wide spectrum of pathological conditions [3,58,59]. It is important to note that hemin is released by oxidized ferric (Fe 3+ ) hemoglobin in the human body [60], and hemin has been demonstrated to initiate the Y → H morphological transition of C. albicans in vitro [13,14], which is likely to facilitate the superficial invasion of the oral mucosa by C. albicans in vivo [50,61,62].…”
Section: Discussionmentioning
confidence: 99%